2018
DOI: 10.1080/13543776.2018.1424135
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the development of histamine H3 receptor antagonists/inverse agonists: a patent review (2013-2017)

Abstract: Since years, ligands blocking histamine H receptor (HR) activity (antagonists/inverse agonists) are interesting targets in the search for new cures for CNS disorders. Intensive works done by academic and pharmaceutical company researchers have led to many potent and selective HR antagonists/inverse agonists. Some of them have reached to clinical trials. Areas covered: Patent applications from January 2013 to September 2017 and the most important topics connected with HR field are analysed. Espacenet, Patentsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 109 publications
0
14
0
Order By: Relevance
“…Thus, extensive preclinical studies have assessed the role of H 3 receptors in working memory. However, very few such studies have been conducted in humans, and the published clinical studies of H 3 receptor antagonist/inverse agonists have shown the mixed results of cognitive improvements in neuropsychiatric diseases ([ 4 , 5 ] for review). For example, some studies reported the positive effects of H 3 receptor drugs in episodic memory in Alzheimer’s disease, while others found no beneficial effects examined by various drugs in different diseases [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, extensive preclinical studies have assessed the role of H 3 receptors in working memory. However, very few such studies have been conducted in humans, and the published clinical studies of H 3 receptor antagonist/inverse agonists have shown the mixed results of cognitive improvements in neuropsychiatric diseases ([ 4 , 5 ] for review). For example, some studies reported the positive effects of H 3 receptor drugs in episodic memory in Alzheimer’s disease, while others found no beneficial effects examined by various drugs in different diseases [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, very few such studies have been conducted in humans, and the published clinical studies of H 3 receptor antagonist/inverse agonists have shown the mixed results of cognitive improvements in neuropsychiatric diseases ([ 4 , 5 ] for review). For example, some studies reported the positive effects of H 3 receptor drugs in episodic memory in Alzheimer’s disease, while others found no beneficial effects examined by various drugs in different diseases [ 5 ]. These unclear therapeutic effects may come from the complex biology and pharmacology of H 3 receptor, such as the heterogeneity of isoforms and the different profile of drug activity (full agonists, partial agonists, neutral antagonists, inverse agonists and protean ligands) [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that the complex cytoarchitectonic, arrangement and distribution of histamine receptors in different brain regions is responsible for some of the apparently controversial mnemonic effects of, for instance, H 3 receptor antagonists. Pitolisant , an H 3 antagonist, is a newly marketed compound for the treatment of narcolepsy (Kollb‐Sielecka et al, 2017), and preclinical and clinical trials have suggested the potential utility of this class of drugs in neuropsychiatric diseases (Łażewska and Kieć‐Kononowicz, 2018). Dysfunctional fear responses have a crucial role in many mental disorders, and new insights suggest that drug interventions, for example, propranolol , during the reconsolidation of reactivated fear memories may increase the efficacy of therapeutic interventions (Kindt et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Much effort has been devoted to developing potent and selective H 3 R inhibitors (antagonists/inverse agonists) [ 3 , 4 , 5 ], and pitolisant ( 2 , Figure 1 ) was recently authorized in Europe as a medicine for treating narcolepsy with or without cataplexy [ 6 ]. Further research is needed to better understand the functions of the histaminergic system in CNS-related disorders and to advance useful H 3 antagonists into clinical trials and the market [ 7 ].…”
Section: Introductionmentioning
confidence: 99%